Putative hAPN receptor binding sites in SARS_CoV spike protein. - Yu Xiao-Jing; Luo Cheng; Lin Jian-Cheng; Hao Pei; He You-Yu; Guo Zong-Ming; Qin Lei; Su Jiong; Liu Bo-Shu; Huang Yin; Nan Peng; Li Chuan-Song; et al. (Acta Pharmacologica Sinica, 2016)
AIM: To obtain the information of ligand-receptor binding between the S protein of SARS-CoV and CD13, identify the possible interacting domains or motifs related to binding sites, and provide clues for studying the functions of SARS proteins and designing anti-SARS drugs and vaccines. METHODS: On the basis of comparative genomics, the homology search, phylogenetic analyses, and multi-sequence alignment were used to predict CD13 related interacting domains and binding sites in the S protein of SARS-CoV. Molecular modeling and docking simulation methods were employed to address the interaction feature between CD13 and S protein of SARS-CoV in validating the bioinformatics predictions. RESULTS: Possible binding sites in the SARS-CoV S protein to CD13 have been mapped out by using bioinformatics analysis tools. The binding for one protein-protein interaction pair (D757-R761 motif of the SARS-CoV S protein to P585-A653 domain of CD13) has been simulated by molecular modeling and docking simulation methods. CONCLUSION: CD13 may be a possible receptor of the SARS-CoV S protein, which may be associated with the SARS infection. This study also provides a possible strategy for mapping the possible binding receptors of the proteins in a genome.